2009
DOI: 10.1124/dmd.108.024695
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphomimetic Mutation at Threonine-57 Abolishes Transactivation Activity and Alters Nuclear Localization Pattern of Human Pregnane X Receptor

Abstract: ABSTRACT:The pregnane X receptor (PXR) plays crucial roles in multiple physiological processes. However, the signaling mechanisms responsible are not well defined; it is most likely that multiple functions of PXR are modulated by its phosphorylation. Therefore, we sought to determine whether mutation at a highly conserved Thr ) and show p70 S6K phosphorylation and regulation of hPXR transactivation to support the notion that phosphorylation plays important roles in regulating hPXR function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 44 publications
4
82
0
1
Order By: Relevance
“…The CMV-Renilla luciferase plasmid was purchased from Promega (Madison, WI). Transient transfections were performed using FuGENE 6 (Roche Diagnostics, Indianapolis, IN) as described previously (Lin et al, 2008;Pondugula et al, 2009b). In brief, transfections were performed in 6-well culture plates with 2 g of total plasmid DNA per well.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CMV-Renilla luciferase plasmid was purchased from Promega (Madison, WI). Transient transfections were performed using FuGENE 6 (Roche Diagnostics, Indianapolis, IN) as described previously (Lin et al, 2008;Pondugula et al, 2009b). In brief, transfections were performed in 6-well culture plates with 2 g of total plasmid DNA per well.…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 human liver carcinoma cell line was propagated as described previously (Lin et al, 2008;Pondugula et al, 2009b) in growth media containing Dulbecco's modified Eagle's medium (DMEM) (Invitrogen, Carlsbad, CA) supplemented with 10% fetal bovine serum (HyClone, Logan, UT), 100 U/ml penicillin (Invitrogen), 100 g/ml streptomycin (Invitrogen), 2 mM L-glutamine (Invitrogen), and 1 mM sodium pyruvate (Invitrogen). The pcDNA3-hPXR, FLAGpcDNA3-hPXR, and pGL3-CYP3A4-luc (CYP3A4 luciferase reporter) plasmids were generated as described previously (Lin et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic approach to mutating serine/threonine (S/T) residues to aspartic acid (D) revealed that Ser8Asp, Thr57Asp, Ser208Asp, and Thr408Asp resulted in a decrease in PXR transactivation (Lichti-Kaiser et al 2009a). Notably, we determined the phosphomimetic mutant of PXR, Thr57Asp, also exhibited an altered pattern of subcellular localization (Pondugula et al 2009a). Collectively, phosphorylation of PXR confers a negative regulatory effect, possibly through altering its pattern of subcellular localization or affecting its interaction with corepressors or coactivators.…”
Section: 3mentioning
confidence: 99%